Detection of Fungal Infections in Gloriosa Superba Plant Using the Convolution Neural Network Model - Guillermo Napoleón Pelaez-Diaz; Rosa Vílchez-Vásquez; Antonio Huaman-Osorio; R. Mahaveerakannan; S. Pushpa; Nilesh Shelke; Sumitha Jagadibabu; Jenifer Mahilraj (Journal of Food Quality)
Herbal treatments’ efficacy, safety, and mild side effects are also high priorities in primary care. Furthermore, as the world’s population expands, food production becomes more difficult. We need to use innovative biotechnology-based fertilization technologies to boost food production output. Gloriosa superba is one of the most well-known plants for its antibacterial and medicinal capabilities. The money plant is also known as the Gloriosa superba. We used a deep learning-based convolution neural network (CNN) classifier model to optimize the CNN algorithm parameter for better prediction. The enhanced particle swarm optimization (PSO) technique was used for optimization. Scale-invariant feature transform (SIFT) was used to extract the fungal spotted area. Digital camera with a high resolution acquires 300 dataset photographs from different villages in India for this investigation. Using a real-time fungal-affected image to train and test the model, different parametric measures are used to assess the model’s performance. The categorization accuracy obtained in this experiment was 99.32 percent.